School-based physical activity intervention for older adolescents: rationale and study protocol for the Burn 2 Learn cluster randomised controlled trial. Issue 5 (22nd May 2019) - Leahy, Angus A; Eather, Narelle; Smith, Jordan J; Hillman, Charles; Morgan, Philip J; Nilsson, Michael; Lonsdale, Chris; Plotnikoff, Ronald C; Noetel, Michael; Holliday, Elizabeth; Shigeta, Tatsuya T; Costigan, Sarah A; et al.
Abstract : Introduction: This trial aims to investigate the impact of a school-based physical activity programme, involving high-intensity interval training (HIIT), on the physical, mental and cognitive health of senior school students. Methods and analysis: The Burn 2 Learn (B2L) intervention will be evaluated using a two-arm parallel group cluster randomised controlled trial with allocation occurring at the school level (to treatment or wait-list control). Schools will be recruited in two cohorts from New South Wales, Australia. The trial will aim to recruit ~720 senior school students (aged 16–18 years) from 20 secondary schools (ie, 10 schools per cohort). A range of implementation strategies will be provided to teachers (eg, training, equipment and support) to facilitate the delivery of HIIT sessions during scheduled classes. In phase I and II (3 months each), teachers will facilitate the delivery of at least two HIIT sessions/week during lesson-time. In phase III (6 months), students will be encouraged to complete sessions outside of lesson-time (teachers may continue to facilitate the delivery of B2L sessions during lesson-time). Study outcomes will be assessed at baseline, 6 months (primary end point) and 12 months. Cardiorespiratory fitness (shuttle run test) is the primary outcome. Secondary outcomes include: vigorous physical activity, muscular fitness, cognition and mental health. A subsample of students will (i) provide hair samples to determine their accumulated exposure to stressful events and (ii) undergo multimodal MRI to examine brain structure and function. A process evaluation will be conducted (ie, recruitment, retention, attendance and programme satisfaction). Ethics and dissemination: This study has received approval from the University of Newcastle (H-2016–0424) and the NSW Department of Education (SERAP: 2017116) human research ethics committees. Trial registration number: ACTRN12618000293268; Pre-results.